Formulasi dan Karakterisasi Nanogel Ekstrak Etanol Daun Katuk (Breynia androgyna L.) - Fika Nur Hasyaeni; Aulia Fikri Hidayat; Ratih Aryani (Bandung Conference Series: Pharmacy, 2024)
Abstract. Katuk leaf is a medicinal plant in Southeast Asia, including Indonesia. Nanogels are gels with small particle sizes and large surface areas that can increase the penetration of active compounds. Objective: Formulation and characterization of nanogel preparation of ethanol extract of katuk leaf (Breynia androgyna L.). Methods: Simplisia of katuk leaves were dried, characterized, and screened. Extraction by maceration method using 96% ethanol. Formulation of nanoparticle preparations with sodium alginate and CaCl2, concentration variations (4:1; 3:2; 2:3; 1:4). Nanoparticle characteristics: organoleptic, transmittance, particle size, and zeta potential. Evaluation of nanogels: organoleptic, homogeneity, pH, viscosity, spreadability, and stability. Results: The results of the characteristics of katuk leaf simplisia are moisture content, total ash, acid insoluble ash, water soluble essence, ethanol soluble essence, drying shrinkage of 8.26, 6.96, 0.87, 31.55, 26.59, and 9.09% respectively. Simplisia and extracts contain alkaloids, flavonoids, saponins, anthraquinones, monoterpenoids/sesquiterpenoids, tannins, polyphenolics, and triterpenoids. The characteristics of the best nanoparticle formula: percent transmittance of 93.33%, particle size of 209nm, and zeta potential of -41.4mV. The resulting nanogel preparation: clear yellow, odorless, homogeneous, pH 6.4-6.9, spreadability 6.08-6.17cm, viscosity 3812-3846 cPs, stable during 1-week storage. Conclusion: The ethanol extract of katuk leaves can be formulated in a nanogel preparation that is stable during storage and meets the requirements for evaluating the physical properties of nanogel preparations. Abstrak. Daun katuk dikenal sebagai tumbuhan obat di Asia Tenggara, termasuk Indonesia. Nanogel adalah gel dengan ukuran partikel kecil dan luas permukaan luas sehingga dapat meningkatkan penetrasi senyawa aktif. Tujuan: Formulasi dan karakterisasi sediaan nanogel ekstrak etanol daun katuk (Breynia androgyna L.). Metode: Simplisia daun katuk dilakukan proses pengeringan, karakterisasi dan skrining. Ekstraksi dengan metode maserasi menggunakan etanol 96%. Formulasi sediaan nanopartikel dengan natrium alginat dan CaCl2 dengan variasi konsentrasi (4:1; 3:2; 2:3; 1:4). Karakteristik nanopartikel meliputi organoleptik, uji transmitan, ukuran partikel dan potensial zeta. Evaluasi nanogel meliputi organoleptik, homogenitas, pH, viskositas, daya sebar, dan stabilitas. Hasil: Hasil karakteristik simplisia daun katuk yaitu kadar air, abu total, abu tidak larut asam, sari larut air, sari larut etanol, susut pengeringan berturut-turut 8,26, 6,96, 0,87, 31,55, 26,59 dan 9,09%. Simplisia dan ekstrak mengandung alkaloid, flavonoid, saponin, antrakuinon, tanin, monoterpenoid/seskuiterpenoid, polifenolat serta triterpenoid. Hasil karakteristik formula nanopartikel terbaik meliputi persen transmitan 93,33%, ukuran partikel 209nm, dan potensial zeta -41,4mV. Sediaan nanogel yang dihasilkan berwarna kuning jernih, tidak berbau, homogen, pH 6,4-6,9, daya sebar 6,08-6,17cm, viskositas 3812-3846 cPs, stabil selama penyimpanan 1 minggu. Kesimpulan: Ekstrak etanol daun katuk dapat diformulasikan dalam sediaan nanogel yang stabil selama penyimpanan dan memenuhi syarat evaluasi sifat fisik sediaan nanogel.